Peran Kepuasan Pelanggan Sebagai Mediator Dalam Pengaruh Kualitas Layanan Terhadap Loyalitas Pengguna JasaAplikasi Gofood Di Kalangan Mahasiswa - Tri Marhaeni; Aprillina Sanjaya; Alfinda Dewi A; Mita Oktaviani (STIA MALANG, 2026)
This study analyzes the effect of service quality on customer loyalty, with satisfaction as a mediating variable, among GoFood users among STIA Malang students. A quantitative explanatory method using SEM-PLS was used on a purposive sample of active students. The research instrument was proven valid and reliable, as evidenced by the outer loading value exceeding 0.70, the AVE exceeding 0.50, and the CR exceeding 0.70. The results support all proposed hypotheses: service quality significantly influences satisfaction (β = 0.62); satisfaction significantly influences loyalty (β = 0.58); service quality directly influences loyalty (β = 0.31); and satisfaction mediates the effect of service quality on loyalty (indirect β = 0.36). The proposed model yielded R² values of 0.39 for satisfaction and 0.52 for loyalty, indicating a moderate to strong model fit.These findings strengthen SERVQUAL theory, Oliver's Loyalty Model, and the Service-Profit Chain, and are consistent with previous research. In practice, satisfaction has been shown to be a key variable bridging service quality with GoFood user loyalty